Investigation of psychological factors related to compassion fatigue, burnout, and compassion satisfaction among nurses - Aslı Yeşil; Şehrinaz Polat (BMC, 2023)
Abstract Background While compassion fatigue is evaluated positively in nurses, compassion fatigue and burnout are undesirable from the viewpoint of professionals, service providers, institutions and ultimately society. It is necessary to identify the factors that lead to undesirable results and to reduce their effects. This study aimed to investigate nurses' levels of compassion fatigue, compassion satisfaction, burnout, various psychopathological symptom levels, coping skills, and the relationship between them. Methods This was a descriptive cross-sectional study. The participants were 356 nurses working in tertiary university hospitals in Istanbul (Türkiye). The Healthcare Professional Information Form, ProQOL-IV, Brief Symptom Inventory, and the Coping Orientations to Problems Experienced scale were used to collect data. Descriptive statistics, correlation analyses, and regression models were used to analyze the data. Results According to the findings, low-level burnout, moderate-high compassion satisfaction, and low-moderate compassion fatigue symptoms were detected. Low-level anxiety, depression, somatization, hostility, and negative self-esteem were found. According to the results of regression analysis, mental disengagement and planning coping strategies positively affect the synergy of compassion fatigue (p < 0.05). Turning religion and restraint coping have a positive effect on compassion fatigue (p < 0.05). While depression has a positive effect on burnout, nurses' positive reinterpretation and growth strategy is effective in coping with burnout (p < 0.05). Positive reinterpretation and growth coping strategies are also effective in increasing job satisfaction (p < 0.05). Conclusions Nurses showing somatization symptoms are risk factors for compassion fatigue, and nurses showing depression symptoms are risk factors for burnout, so they should be closely monitored and should be given support. Mental disengagement and planning coping strategies can reduce compassion fatigue, and positive reinterpretation and growth methods can reduce burnout and increase compassion satisfaction. It may be useful to provide counseling and training for nurses to use the right coping methods.